2020
DOI: 10.22454/fammed.2020.137698
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding Expectations: Students Underrepresented in Medicine at University of Utah Health

Abstract: Background and Objectives: The University of Utah (UU) serves an increasingly diverse state and houses the only public medical school, dental school, and college of pharmacy in the state. Utah’s diversity in the health professions lags behind the diversity of its general population, and the nation. Methods: The Health Sciences Learning, Engagement, Achievement, and Progress (HS-LEAP) Program is a 4-year undergraduate pipeline program intended to increase racial and ethnic diversity in the health professions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…1 These results are comparable or better than outcomes from similar pathway programs in advancing students to graduate programs and medical school acceptance. 15 , 23 Eleven BxCHL alumni have obtained their medical degree and the majority will be training in primary residency programs. The BxCHL model was successfully replicated for another program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 These results are comparable or better than outcomes from similar pathway programs in advancing students to graduate programs and medical school acceptance. 15 , 23 Eleven BxCHL alumni have obtained their medical degree and the majority will be training in primary residency programs. The BxCHL model was successfully replicated for another program.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to near-peer mentors is known to contribute to the success of socioeconomically disadvantaged and URM students pursuing health care careers. 9 , 15 Also, programs that expose students to health care environments have a positive impact on their decision to pursue health care careers. 20–22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other programs suggested that the admission requirements needed to be reexamined to ensure that the existing criteria were not unintentionally screening out otherwise qualified students (NIGMS, 2021). Pathways program admission personnel need to be educated just as university admission committees are on implicit bias; they need to implement admission practices that reduce biases and have members who identify as underrepresented (* Bliss et al, 2020;NIGMS, 2021). The undergraduate application process had a variety of metrics including (but not limited to) the candidate's research knowledge, letters of recommendations, grade point average (GPA), and standardized test scores.…”
Section: Comprehensive Selection Processmentioning
confidence: 99%
“…Senior mentors are those who have significantly more experience in their field and use this experience to mentor those who are not as far along in their specialty. A couple of pathways programs for undergraduate students used peer mentorship (Apprey et al, 2014;*Bliss et al, 2020), while other programs, including those for school-aged children, used near-peer mentorship as a modality (Knowledge Is Power Program Public Charter Schools [KIPP], undated; University of Maryland, Baltimore County [UMBC], undated). In tiered mentorship structures, there are mentors at multiple levels, as well as near-peer and senior mentors.…”
Section: Types Of Mentorsmentioning
confidence: 99%